Field Investigation on Limestone Treatment using Fissure Grouting Method - Ananthan, Prakash; Wong, Leong Sing (International Journal of Engineering and Technology, 2018)
This paper documents a field study on fissure grouting for limestone with a specific aim to investigate grout injection into the rock in order to reduce its permeability. The study focused on grouting in advance of excavation and it is applicable to grouting carried out to seal exposed rock surfaces. Investigation concentrated on the need to carry out fissure grouting to seal off excessive water entering the excavation through fractured rocks. In this case, the grout mixtures involved a combination of Ordinary Portland cement (OPC) and bentonite with appropriate amount of water. The grouting was performed at each stage until the grout flow rate and pressure reached a constant level for the last five minutes. If the stage of grouting in a borehole required more grout, this implies that there exist more fissure and cracks in the rock. The ultimate outcome of the rock fissure grouting was to obtain a good feed into limestone rock fissures, and thus, the process involved high injection pressure. The minimum grouting pressure was indicated as the hydrostatic pressure plus line loss pressure. To ensure that the outcome was achieved, it was recommended for an additional two bar pressure to be maintained as hydrostatic pressure.Â